PERANCANGAN E-MODUL BERBASIS ANDROID UNTUK MEMFASILITASI PENINGKATAN KEMAMPUAN SPASIAL MATEMATIS SISWA SMP KELAS VIII PADA MATERI GEOMETRI - Husna, Laelatul; Khotimah, Khotimah (LPPM Universitas Bina Bangsa, 2025)
The purpose of this study is to determine the feasibility, student responses, and improvement in spatial mathematical abilities through the use of an Android-based e-module for facilitating the spatial skills of eighth-grade students in geometry. This research is a development study using the R&D (Research and Development) approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects were eighth-grade students at SMP PGRI Kramatwatu. The research instruments included Android-based e-module evaluation sheets to assess the module's feasibility and student responses, as well as test instruments to measure students' spatial mathematical abilities. Based on the results, the Android-based e-module was considered highly feasible, with a material expert rating of 80.72% and a media expert rating of 82.5%, yielding an average score of 81.61%. The percentage of student responses in the limited trial was 78.83%, and in the field, trial was 77.09%, both falling under the